Conversion Factors for Calculating the Price Payable for Harvested Bamboo (Bambusa Bambos) from the Notified Price for Standing Bamboo in Kerala forests - Krishnankutty, C. N.; Manoharan, T. M.; Chundamannil, Mammen (Indian Forester, 2012)
Bamboo (Bambusa bambos) from the forests of Kerala is allotted to the pulp industry by the government and its selling price is notified annually per metric tonne of standing bamboo. Weight of harvested bamboo is recorded at the factory gate after several days of felling. Due to loss of moisture from harvested bamboo, delay in weighing reduces its weight from that in the standing condition. The existing formula for accounting the change in weight is arbitrary and unscientific. This paper presents a set of better conversion factors which can be used to determine either the standing weight from the weight of harvested bamboo or the price payable for harvested bamboo from the notified price, after any period since harvest. Use of these conversion factors eliminates loss to either the government or pulp industry. For calculating the price payable for harvested bamboo, the notified price has to be multiplied by the conversion factor corresponding to its moisture content. For practical purposes, where the weight of harvested bamboo has already been converted to its weight at the standardised 50% moisture content, only the conversion factor of 0.9129 needs to be remembered to arrive at the price payable in any year. It is suggested that the selling price may henceforth be notified per metric tonne of bamboo at 50% moisture content, to avoid the need for any conversion factor.